Estudo das características empresariais sob a perspectiva do gênero do município de Itaú-RN - Costa, Laize Cristina Silva da (Universidade Federal Rural do Semi-Árido, 2018)
With the big drop in jobs in the country people to escape the unemployment has been become entrepreneurs. In this scenario, this study aims to analyze the business and features the profile of entrepreneurs from the Mall of the municipality of Itaú/RN, about the genre. The methodology of this work consists of descriptive research and survey data quantitatively, making use of a questionnaire that covers several features to meet the city's commercial profile. 26 questionnaires were obtained from different projects and analyzing the characteristics found it was noted that there is a growth of the female figure in the entrepreneurial field and that even the male figure still being in great proportion in says respect to entrepreneurship this scenario has been suffering big change in recent years.
Keywords: Empreendedorismo; Município de Itaú; Empreendimentos; Entrepreneurship; Municipality of Itaú; Enterprise; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA